Health Interview Survey, 1967 ([Verlag nicht ermittelbar], 2010)
The purpose of the Health Interview Survey is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive. There are six types of records in the 1967 survey, each in a separate data file. The variables in the Household file (Part 1) include type of living quarters, size of family, number of families in the household, presence of a telephone, number of unrelated individuals, and region. The Person file (Part 2) includes information on sex, age, race, marital status, Hispanic origin, education, veteran status, family income, family size, major activities, health status, activity limits, employment status, and occupation. These variables are found in the Condition file (Part 3) and the Hospital Episode file (Part 4) as well. The Person file (Part 2) also supplies data on height, weight, bed days, doctor visits, hospital stays, years at residence, and region variables. The Condition file (Part 3) contains information for each reported health condition, with specifics on injury and accident reports. The Hospital Episode file (Part 4) provides information on medical conditions, hospital episodes, type of service, type of hospital ownership, date of admission and discharge, number of nights in hospital, and operations performed. The Doctor Visit file (Part 5) documents doctor visits within the time period and identifies acute or chronic conditions. The Home Care file (Part 6) documents basic demographic information, eating habits, in-home mobility, hospital visits, and the extent that basic living activities and needs are performed with or without aid.